The Use of Quizizz in Arabic Sound Tests and Vocabulary Tests to Increase Student Participation at MIN 3 Nagan Raya - Fadhil, Ardiman (Jurnal Profesi Guru Indonesia, 2025)
Arabic language learning requires mastery of fundamental components, particularly speech sounds and vocabulary, which must be assessed through appropriate evaluation methods. However, language tests at the elementary school level are still commonly conducted using conventional approaches that tend to limit students’ active participation. This study aims to describe the use of Quizizz in speech sound and vocabulary tests in Arabic language learning and to analyze its contribution to improving students’ participation at MIN 3 Nagan Raya. This research employed a qualitative approach using documentation studies, classroom observations, and interviews with Arabic language teachers and fifth- and sixth-grade students. The findings indicate that the implementation of Quizizz in speech sound and vocabulary tests creates a more interactive, engaging, and enjoyable evaluation atmosphere. Students demonstrated higher levels of participation, reflected in active involvement, sustained focus during the test, and increased motivation and self-confidence. In speech sound tests, Quizizz supported students in recognizing and distinguishing Arabic sounds through clear audio stimuli, while in vocabulary tests, it facilitated students’ understanding of word meanings and usage in context. Therefore, Quizizz functions not only as an assessment tool but also as a pedagogical strategy that enhances students’ active participation in Arabic language learning.